Design and simulation of UWB microstrip patch antenna for Ku/K bands applications - Mohammed El Jourmi; Hassan Ouahmane; Fouad Kharroubi (Institute of Advanced Engineering and Science, 2019)
In this paper, a compact Rectangular Microstrip Patch Antenna (RMPA) fed by microstrip line has been designed to operate for Ku/K bands applications. The proposed antenna is slotted and optimized to reach a large bandwidth and cover various applications such as 5G communication (in frequency range 24.25-27.5 GHz), fixed and mobile satellite, radionavigation, space research, radiolocation etc. In this design, the substrate used is FR4 with a relative permittivity of 4.4 and a thickness of 1.6 mm. The slotted RMPA has been simulated using Advanced Design System (ADS) software and the obtained results are presented and discussed. The proposed antenna achieves a return loss less than -10 dB and VSWR (voltage standing wave ratio) < 2 in frequency range from 16.58 to 25.29 GHz. The percentage bandwidth provided by the proposed microstrip antenna is 41.61%.